CINTA DALAM PERSPEKTIF FILSAFAT EKSISTENSIALISME JEAN-PAUL SARTRE - Gede Agus Siswadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Some philosophers explain love as something beautiful. Love is defined as the spirit or basis of human life. Love gives a cheerful nuance that has an impact on human harmony and peace. However, it is different from the view of the existentialist philosopher Jean-Paul Sartre who thinks love is not something beautiful. The method used in this research is philosophical hermeneutics by exploring the thoughts of Jean-Paul Sartre related to love. The results of this study are. First, Sartre defines love as something that causes conflict. It is based on Sartre's opinion, which says humans are not free and always become objects in a relationship called love. Second, love is self-deception because it causes humans to be inauthentic and enslaved by love. Third, Sartre explains that sexual relations are the complete surrender of their existence to others.